2010
DOI: 10.1111/j.1600-0625.2010.01130.x
|View full text |Cite
|
Sign up to set email alerts
|

Strong exercise stress exacerbates dermatitis in atopic model mice, NC/Nga mice, while proper exercise reduces it

Abstract: Atopic dermatitis is well known to exacerbate by stress. How the influence of exercise stress on the skin symptoms in patients with atopic dermatitis has not been clarified. The purpose of our research is to investigate how different strength of exercise stress acts on atopic dermatitis. Specific pathogen-free (SPF) and conventional NC/Nga male mice were used for the experiments. Conventional mice but not SPF group spontaneously develop dermal symptom similar to that of patients with atopic dermatitis at their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…In the aggravation of atopic dermatitis in NC/Nga mice, COEW does not seem to affect the plasma IgE concentrations. In the recent study, while the AD score was suppressed in conventional NC/Nga mice, plasma IgE concentrations was maintained to high levels [20], which phenomenon supports our data.…”
Section: Skin Hydrating Effects Of Corchorus Olitorius Extract In a Msupporting
confidence: 79%
“…In the aggravation of atopic dermatitis in NC/Nga mice, COEW does not seem to affect the plasma IgE concentrations. In the recent study, while the AD score was suppressed in conventional NC/Nga mice, plasma IgE concentrations was maintained to high levels [20], which phenomenon supports our data.…”
Section: Skin Hydrating Effects Of Corchorus Olitorius Extract In a Msupporting
confidence: 79%
“…The plasma level of β-End was found to be increased in mice with a mild stress load [9]. This suggested the possibility that β-End contributed to the reduction of the AD-like symptoms.…”
Section: Introductionmentioning
confidence: 70%
“…Furthermore, it has been suggested that there are relationships among AD, β-End and allergies [7,8]. In our previous study using NC/Nga mice, we showed that AD-like symptoms were exacerbated by strong stress and reduced by mild stress [9].…”
Section: Introductionmentioning
confidence: 99%
“…Allergic diarrhea was induced by repeated intragastric administration of ovalbumin in BALB/c mice. Contact hypersensitivity was evaluated by measuring ear swelling after topical application of 2, 4-dinitrofluorobenzene in NC/Nga mice, which are often used as a mouse model of AD (Jin et al, 2011;Orita et al, 2010). Arthritis was induced by intradermal injection of bovine type-II collagen emulsified with complete Freund's adjuvant in DBA/1J mice.…”
Section: Wwwintechopencommentioning
confidence: 99%